Evaluation of Sports and Health Physical Education Learning Programs in Junior High Schools in Sampolawa District - Alirman Sarpan; Rumini Rumini; Mugiyo Hartono (JUARA : Jurnal Olahraga, 2022)
This study aims to see how the PJOK learning process in schools from the planning stage of learning and implementation of learning to evaluation through antecedents evaluation, transaction evaluation, and outcomes evaluation. This research is a program evaluation using the Stake evaluation model with the stages of context evaluation, process evaluation, and outcomes evaluation. Data were collected by using observation, interview, and documentation methods. Qualitative data analysis techniques have four components: data collection, data reduction, data presentation, and conclusion. The results showed that, in general, the PJOK learning activity program at the State Junior High Schools throughout the Sampolawa District had been running well by the applicable curriculum. The conclusion of learning activities for physical education, sports and health at State Junior High Schools in Sampolawa District, in the context of teachers always making and collecting learning tools, program objectives, policies have been implemented well, and infrastructure facilities are still lacking. In implementing activities by applicable laws and regulations, the implementation and coordination carried out are by the learning plans, materials and performance processes, but facilities and infrastructure are still lacking. The overall evaluation outcomes are good in the academic field; student learning outcomes are by the minimum completeness criteria.